2013
DOI: 10.1542/peds.2012-1298
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Ischemic-Hypoxic Conditions and Attention-Deficit/Hyperactivity Disorder

Abstract: These findings suggest that IHCs, especially birth asphyxia, respiratory distress syndrome, and preeclampsia, are independently associated with ADHD. This association was strongest in preterm births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
101
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 58 publications
11
101
1
5
Order By: Relevance
“…Both term and preterm HI populations show heightened incidence for an array of cognitive and behavioral deficits, including language impairments [32,33,35,36,37,109,110], attentional problems associated with ADHD [42,43,44,45,46,47,54,63,111] and memory impairments [33,38,39,40,56,57,64,112,113]. In the current series of studies, we focus specifically on working memory impairments associated with neonatal HI injury in a rat model.…”
Section: Resultsmentioning
confidence: 99%
“…Both term and preterm HI populations show heightened incidence for an array of cognitive and behavioral deficits, including language impairments [32,33,35,36,37,109,110], attentional problems associated with ADHD [42,43,44,45,46,47,54,63,111] and memory impairments [33,38,39,40,56,57,64,112,113]. In the current series of studies, we focus specifically on working memory impairments associated with neonatal HI injury in a rat model.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41] The mechanism of how tobacco smoke affects the fetal brain remains unclear, 6,33 but it has been hypothesized that perinatal events resulting in hypoxia may affect brain development and lead to ADHD. 11,42,43 Such risk factors include threatened abortion, threatened preterm labor, preeclampsia, prematurity, intrauterine growth retardation, low Apgar scores, and fetal distress. 35,44,45 Our study contradicts some of these findings in that we found no association with acute events around delivery except for the rare event of cord prolapse in girls, also suggested in a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…35,44,45 Our study contradicts some of these findings in that we found no association with acute events around delivery except for the rare event of cord prolapse in girls, also suggested in a recent study. 11 Maternal preeclampsia and genitourinary tract infections have been associated with other neurodevelopmental disorders, including ADHD, 12,46 where an inflammatory cascade affecting fetal brain development has been suggested. In our fully adjusted model, both preeclampsia and maternal genitourinary tract infections were associated with an elevated risk of ADHD irrespective of gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental insufficiency and fetal growth restriction are associated with altered angiogenic [Conde-Agudelo et al, 2013], dopaminergic [Vucetic et al, 2010], neurotrophic [MalamitsiPuchner et al, 2007], and inflammatory responses [Amarilyo et al, 2011], and numerous poor neurodevelopmental outcomes [Baschat, 2011]. Prenatal ischemia-hypoxia is a common element to multiple early risk factors for ADHD including maternal smoking [Bush et al, 2000] and maternal alcohol use during pregnancy [Bosco and Diaz, 2012] as well as ischemia-hypoxia related obstetric complications [Pineda et al, 2007;Rennie et al, 2007;Getahun et al, 2013]. Consistent with the Developmental Origins of Health and Disease (DOHaD) framework [Gluckman et al, 2004;Mill et al, 2008;Swanson and Wadhwa, 2008;Swanson et al, 2009;Wadhwa et al, 2009], the association between lower birth weight and ADHD may arise from prenatal ischemia-hypoxia.…”
Section: Introductionmentioning
confidence: 99%